2020
DOI: 10.3390/jcm9030627
|View full text |Cite
|
Sign up to set email alerts
|

Going Beyond Conventional Mammographic Density to Discover Novel Mammogram-Based Predictors of Breast Cancer Risk

Abstract: This commentary is about predicting a woman’s breast cancer risk from her mammogram, building on the work of Wolfe, Boyd and Yaffe on mammographic density. We summarise our efforts at finding new mammogram-based risk predictors, and how they combine with the conventional mammographic density, in predicting risk for interval cancers and screen-detected breast cancers across different ages at diagnosis and for both Caucasian and Asian women. Using the OPERA (odds ratio per adjusted standard deviation) concept, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 38 publications
6
34
0
Order By: Relevance
“…On the other hand, the Cirrocumulus and Cirrus risk gradients both remained similar to what they were when fitted alone [2-6]. We concluded that “conventional mammographic density predicts interval cancer due to its role in masking, while the new mammogram-based risk measures could have a causal effect on both interval and screen-detected breast cancer” [7].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…On the other hand, the Cirrocumulus and Cirrus risk gradients both remained similar to what they were when fitted alone [2-6]. We concluded that “conventional mammographic density predicts interval cancer due to its role in masking, while the new mammogram-based risk measures could have a causal effect on both interval and screen-detected breast cancer” [7].…”
Section: Introductionmentioning
confidence: 71%
“…For example, when Cirrocumulus and Cirrus were combined to predict breast cancer at on average a younger age (see Table 1), the AUC-equivalent OPERA was 2.28, so the interquartile risk ratio is ∼7-fold. In comparison, the interquartile risk ratio is ∼4-fold for a multigenerational family history risk score in predicting breast cancer before age 50 years, ∼3-fold for the latest polygenic risk score, ∼2-fold for conventional mammographic density, ∼1.5-fold for BRCA1 and BRCA2 mutations, and ∼1.2-fold or less for lifestyle-related risk factors [7,8]. .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of interpretation, the residuals are in effect the risk factor (not the raw measure itself), and the log(OPERA) is the difference between cases and controls in the mean of the standardised residuals; see Appendix [6]. On the other hand, the OR per unadjusted standard deviation is problematic when it is estimated after adjusting for covariates (unless it is adjusted in a way that depends on the correlations between covariates [2,7]) and is prone to misinterpretation; see Discussion.…”
Section: Introductionmentioning
confidence: 99%
“…In countries where screening begins at 50 (e.g., the UK), consideration should be given to offering all women a one-off mammogram at age 40, together with risk estimation to determine future screening frequency. Mammographic density could be assessed automatically using artificial intelligence methods [ 64 , 65 ] and SNPs used only to determine precise risk where needed. The trials of risk and density-adapted screening and determination of the value of supplemental imaging techniques, such as whole breast ultrasound, contrast-enhanced mammography and abbreviated MRI, would further refine the management advice offered to women with high MD.…”
Section: Discussionmentioning
confidence: 99%